Making the Sustainable Development Goals Consistent with Sustainability - Wackernagel, Mathis; Hanscom, Laurel; Lin, David (Frontiers in Energy Research, 2017)
The UN’s Sustainable development Goals (SDGs) are the most significant global effort so far to advance global sustainable development. Bertelsmann Stiftung and the sustainable development solutions network released an SDG index to assess countries’ average performance on SDGs. Ranking high on the SDG index strongly correlates with high per person demand on nature (or “Footprints”), and low ranking with low Footprints, making evident that the SDGs as expressed today vastly underperform on sustainability. Such underperformance is anti-poor because lowest-income people exposed to resource insecurity will lack the financial means to shield themselves from the consequences. Given the significance of the SDGs for guiding development, rigorous accounting is essential for making them consistent with the goals of sustainable development: thriving within the means of planet Earth.